Analisis Kemampuan Representasi Siswa SMK - Sonia Aprilia Putri (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2021)
This research aimed to analyze mathematical representation ability of vocational school students in solv mathematical problems of arithmetic series and arithmetic sequence. This is a descriftive research with qualitative approach. Subject of research is student of SMK Negeri 1 Rengasdengklok on class XII TMI 1 selected by purpose sampling. The data anlyzed by using term of data reduction, data display and conclusion drawing. The results showed that: (1) mathematical representation ability of indicator visual representation capability of 61,07%. (2) mathematical representation ability of indicator symbolic representation capability of 75%. (3) mathematical representation ability of indicator verbal representation capability of 51,07%. The highest indicator of mathematical representation ability is symbolic representation, and the lowest indicator of mathematical representation ability is verbal representation. Overall percentage of mathematical representation ability is capability of 62,5%.